Evaluasi Program Pelatihan Pemeliharaan Kendaraan Ringan Sistem Injeksi Di BPVP Surakarta - Nova Aldy Bintang Ramadhan; Bambang Sulistyo (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2026)
Abstract This study evaluates the implementation of the PKRSI training program at BPVP Surakarta using the CIPP model (Context, Input, Process, Product). The research subjects consisted of the program organizers, three instructors, and 32 alumni, with data collected through questionnaires, interviews, documentation, and observation. The instruments were validated through expert judgment, while reliability was tested using Cronbach’s alpha (r = 0.774–0.852). The results show that: (1) Context: The implementation of training has a clear background and legal basis, while the training objectives require improvement; (2) Input: participants’ interest was excellent, motivation was good, instructors’ readiness and competence met the standards, the curriculum followed national standards, and participant selection was applied; (3) Process: participants’ activeness was fairly good, training materials and learning processes were good, and facilities were excellent; (4) Product: participants’ competence improved, training objectives were achieved, graduate employability was good, and the program provided positive benefits for stakeholders. Overall, the PKRSI training was effective, although the training objectives and participant activeness require further enhancement. Abstrak Penelitian ini mengevaluasi pelaksanaan program pelatihan PKRSI di BPVP Surakarta menggunakan model CIPP (Context, Input, Process, Product). Subjek penelitian terdiri dari penyelenggara, tiga instruktur, dan 32 alumni, dengan data dikumpulkan melalui angket, wawancara, dokumentasi, dan observasi. Instrumen divalidasi melalui expert judgement, sedangkan reliabilitas diuji dengan alfa Cronbach (r = 0,774–0,852). Hasil menunjukkan: (1) Context: Pelaksanaan pelatihan memiliki latar belakang dan dasar hukum yang jelas, tujuan pelatihan perlu ditingkatkan; (2) Input: minat peserta sangat baik, motivasi baik, kesiapan dan kompetensi instruktur sesuai standar, kurikulum nasional, dan seleksi peserta; (3) Process: keaktifan peserta cukup baik, materi dan pembelajaran baik, sarana-prasarana sangat baik; (4) Product: peningkatan kompetensi peserta, ketercapaian tujuan, keterserapan lulusan baik, dan manfaat positif bagi pihak terkait. Secara keseluruhan, pelatihan PKRSI dinilai efektif, namun aspek tujuan pelatihan dan keaktifan peserta masih memerlukan peningkatan.